Dietary analysis of the brown bear (Ursus arctos) in Sweden 2015-2018 - Klamárová, Simona (University of South-Eastern Norway, 2019)
Understanding dietary variation is crucial for a better understanding of a species’ ecology as well as for its effective management and conservation. Here I investigate the dietary variation of brown bears (Ursus arctos) in south-central Sweden in relation to year, season, sex and age based on the analysis of 958 bear scats, collected from 2015-2018. The diet of brown bears varied significantly among the seasons and years. Insects and vegetative materials were important food items during the spring/summer season. The most important group of insects were ants, especially Formica spp., with EDEC of 45.06%. The consumption of ungulates was stable between years, but was higher in spring/summer, in accordance with the calving season of moose (Alces alces). Berries (in order of importance: bilberries, lingonberries, crowberries) represented the most important food items (estimated dietary energy content (EDEC): 98.22%) during the pre-denning period in fall. The preference for berries in the fall season was stable between years, but the proportion of species changed, indicating that bears switched between species in relation to environmental conditions. The diet of bears varied also between the sexes, with males consuming comparatively less berries than females, but also more vegetative material compared to females. I found only little effect of age (adult/subadult) on diet choice. The present study is important for the documentation and understanding of feeding habits of brown bears, to understand the potential responses and adaptations of bears to climatic changes, and ultimately, for the effective management and conservation of the species. publishedVersion